2013
DOI: 10.1681/asn.2012080838
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Mesangial Matrix Expansion in Aging Mice and Identification of Far2 as a Candidate Gene

Abstract: Aging of the kidney is associated with renal damage, in particular mesangial matrix expansion (MME). Identifying the genes involved in this process will help to unravel the mechanisms of aging and aid in the design of novel therapeutic modalities aimed at prevention and regression. In this study, structural changes in glomeruli of 24 inbred mouse strains were characterized in male mice at 6, 12, and 20 months of age. Haplotype association mapping was used to determine genetic loci associated with the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…MME , a downregulated gene in the present study, encodes a glycoprotein identified in a variety of normal and malignant tissues. This glycoprotein is particularly abundant in kidney, where it is present on the brush border of proximal tubules and on glomerular epithelium ( 32 ). Amălinei et al ( 33 ) reported that the generation of angiostatin induced by MME was responsible for the prevention of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…MME , a downregulated gene in the present study, encodes a glycoprotein identified in a variety of normal and malignant tissues. This glycoprotein is particularly abundant in kidney, where it is present on the brush border of proximal tubules and on glomerular epithelium ( 32 ). Amălinei et al ( 33 ) reported that the generation of angiostatin induced by MME was responsible for the prevention of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…MME was involved in kidney development, and it is abundantly expressed in the kidney[ 22 ], particularly in podocytes[ 23 ]. Expression of MME at mRNA levels was significantly down-regulated in kidneys of patients with diabetic nephropathy (DN) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the nine loci were associated with diabetic nephropathy in humans. The haplotype association mapping technique used on histological phenotypes in the same inbred strains identified Far2 as being associated with mesangial matrix expansion (MME) in aging mice (Noordmans et al ., 2013 ). MME is a characteristic of glomerular aging and a precursor of glomerulosclerosis.…”
Section: Studies To Date Of Genes Involved In Age-related Kidney Disementioning
confidence: 99%
“…Far2 encodes the protein fatty acyl-coenzyme A reductase 2, which catalyzes the reduction of fatty acyl-CoA to fatty alcohols, a precursor of platelet-activating factor (PAF). Both in vivo and in vitro , this insertion was associated with increased expression of Far2 , leading to upregulation of PAF and TGFβ, which are involved in the pathogenesis of sclerosis (Noordmans et al ., 2013 ). There were some strains in this study with the Far2 insertion but in which MME was not observed suggesting additional genes involved in this phenotype.…”
Section: Studies To Date Of Genes Involved In Age-related Kidney Disementioning
confidence: 99%